LTBK-12. EORTC 26951, RANDOMIZED STUDY OF ADJUVANT PCV AFTER 59.4 GY RADIOTHERAPY: VERY LONG TERM FOLLOW-UP. (22nd November 2019) - van den Bent, Martin; Hoang-Xuan, Khe; Brandes, Alba; Kros, Johan; Kouwenhoven, M C M; Taphoorn, Martin; Delattre, Jean-Yves; Bernsen, Hans; Frenay, Marc; Synhaeve, Nathalie; Weller, Michael; Enting, Roelien; et al.
Abstract: BACKGROUND: Between 1995 and 2002 the EORTC Brain Tumor Group conducted a prospective phase III study on adjuvant procarbazine, CCNU and vincristine (PCV) chemotherapy in anaplastic oligodendroglioma (AOD). A mature follow-up presented in 2012 showed survival benefit of the addition of PCV, in particular in 1p/19q co-deleted tumors and tumors with MGMT promoter methylation. We now present very long term follow-up. MATERIALS AND METHODS: Patients were eligible if locally diagnosed with a newly diagnosed AOD. They were randomized between radiotherapy (RT, 33 x 1.8 Gy) and the same RT followed by 6 cycles PCV (RT/PCV). Primary endpoints were overall survival (OS) and progression free survival (PFS). 1p/19q status (FISH) was determined in 300 patient. Kaplan- Meier technique and Cox modeling were used for long term survival analysis. Primary analyses were adjusted for known prognostic factors. For other analyses no adjustment was performed. RESULTS: With 368 patients included, a median follow-up of 18.4 years and 307 (83%) survival events, median and 20-year survival after RT/PCV versus RT alone were 42.3 mo and 16.8% vs 30.6 months and 10.1% (HR 0.78; 95% CI (0.63, 0.98), adjusted p=0.06). Eighty patients were 1p/19q codel of which 26 (33%) were still alive, in this subgroup median and 20-year survival after RT/PCV versus RT alone were 14 years and 37.1% versus 9.3 years and 13.6% (HR 0.60, 95% CI (0.35, 1.03), unadjusted p=0.06). Twenty year PFS in 1p/19q codel was 31.3% in RT/PCV treated patients and 10.8% in RT only treated patients (HR 0.49, 95% CI (0.29, 0.83), unadjusted p=0.007). In the 1p/19q codel subgroup age, WHO PS and necrosis at pathology were identified to be of independent prognostic value for OS. CONCLUSION: This long term analysis confirms the earlier conclusions and provides data on long term survival in this patient group. In 1p/19q codel patients treated with RT/PCV, the 20-year PFS and OS rates are 31% and 37% respectively.